Slow Expectation-Maximization Convergence in Low-Noise Dynamic Factor Models - Daan Opschoor; Dick van Dijk (Tinbergen Institute, 2023)
This paper addresses the poor performance of the Expectation-Maximization (EM) algorithm in the estimation of low-noise dynamic factor models, commonly used in macroeconomic forecasting and nowcasting. We show analytically and in Monte Carlo simulations how the EM algorithm stagnates in a low-noise environment, leading to inaccurate estimates of factor loadings and latent factors. An adaptive version of EM considerably speeds up convergence, producing substantial improvements in estimation accuracy. Modestly increasing the noise level also accelerates convergence. A nowcasting exercise of euro area GDP growth shows gains up to 34% by using adaptive EM relative to the usual EM.
Keywords: C32; C51; C53; E37; 330; Dynamic factor models; EM algorithm; artificial noise; convergence speed; nowcasting